Diagnostic accuracy of the Cepheid 3-gene host response fingerstick blood test in a prospective, multi-site study: interim results - Sutherland, JS; van der Spuy, G; Gindeh, A; Thuong, NT; Namuganga, AR; Owolabi, O; Mayanja-Kizza, H; Nsereko, M; Thwaites, G; Winter, J; Dockrell, HM; Scriba, TJ; et al. (Oxford University Press, 2021)
Background The development of a fast and accurate, non-sputum-based point-of-care triage test for tuberculosis (TB) would have a major impact on combating the TB burden worldwide. A new fingerstick blood test has been developed by Cepheid (the Xpert MTB Host Response [MTB-HR] prototype), which generates a “TB score” based on messenger RNA (mRNA) expression of 3 genes. Here we describe the first prospective findings of the MTB-HR prototype.